PENGARUH SINDROMA DEPRESI TERHADAP DISFUNGSI EREKSI - Hutagalung, Andre; Elim, Christoffel; Munayang, Herdy (JURNAL BIOMEDIK : JBM, 2009)
Abstract: Normal sexual function is a bio-psycho-social process which is significantly related to the quality of life (QOL). Any disturbance in one of the components can be a disaster in sexual life.  Erectile dysfunction is a disability to get an erection or to maintain the erection well enough for a sexual intercourse, which persists or recurs at least three months conse-cutively due to either psychogenic or organic disturbances, or both. Some psychogenic dis-turbances especially depression, anxiety, and relational distress, play some important roles in ED. Besides that, aging, low testoteron level, physical diseases, and some certain medicines have to be included. Key words: erection, erectile dysfunction, sexual stimulus, depression.     Abstract: Fungsi seksual yang normal merupakan suatu proses biopsikososial yang berkaitan langsung dengan kualitas hidup. Adanya gangguan pada salah satu komponen dapat menjadi malapetaka bagi kehidupan seksual. Disfungsi ereksi dapat dedefinisikan sebagai suatu keti-dakmampuan untuk ereksi atau mempertahankan ereksi yang cukup untuk melakukan hu-bungan seksual yang memuaskan, yang menetap atau berulang paling tidak selama tiga bulan berturut-turut. Gangguan psikogenik khususnya sindroma depresi, ankietas, dan distres relasional berperan penting dalam hal terjadinya disfungsi ereksi. Disamping itu usia lanjut, rendahnya kadar testoteron, penyakit fisik, dan beberapa jenis obat perlu diperhitungkan. Kata kunci: fisiologi ereksi, disfungsi ereksi, stimulus seksual, depresi.